The uneven path to recovery: The sub-Saharan African experience - Michael Danquah; Amina Ebrahim; Maureen Were (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
COVID-19 cases were first confirmed in March 2020 in Ghana, Kenya, and South Africa. These countries put in place several stringent measures, including lockdowns, to contain the spread of the virus. Various policies were also rolled out to address the disruption in economic activities, to mitigate the adverse impacts, particularly on the vulnerable, and to revive the economy. In this paper, we discuss the evolution of the pandemic and containment measures, the subsequent policy responses, and the effectiveness of these policies in Ghana, Kenya, and South Africa. The discussions show that some individuals, particularly informal workers, did not have access to support packages. The moderate relief and economic stimulus packages introduced in these countries to support individuals and businesses seem to have helped some workers to resume their economic activities. However, there seems to have been an uneven recovery in employment and earnings following from these interventions. The experiences from these countries also show that more should have been done to mitigate the impact of the pandemic on informal workers, particularly women, and more needs to be done in future in relation to similar shocks. This includes providing adequate relief for poor and vulnerable people in a quick, safe, and effective manner.
Keywords: R23; N37; O55; J46; 330; COVID-19; sub-Saharan Africa; policy responses; recovery